Yeast and human TATA-binding proteins have nearly identical DNA sequence requirements for transcription in vitro. - Wobbe, C R (1990)
We have analyzed the DNA sequence requirements for TATA element function by assaying the transcriptional activities of 25 promoters, including those representing each of the 18 single-point mutants of the consensus sequence TATAAA, in a reconstituted in vitro system that depends on the TATA element-binding factor TFIID. Interestingly, yeast TFIID and HeLa cell TFIID were virtually identical in terms of their relative activities on this set of promoters. Of the mutated elements, only two had undetectable activity; the rest had activities ranging from 2 to 75% of the activity of the consensus element, which was the most active. In addition, mutations of the nucleotide following the TATAAA core strongly influenced transcriptional activity, although with somewhat different effects on yeast and HeLa TFIID. The activities of all these promoters depended upon TFIID, and the level of TFIID-dependent transcription in vitro correlated strongly with their activities in yeast cells. This suggests that the in vivo activities of these elements reflect their ability to functionally interact with a single TATA-binding factor. However, some elements with similar activities in vitro supported very different levels of transcriptional activation by GAL4 protein in vivo. These results extend the degree of evolutionary conservation between yeast and mammalian TFIID and are useful for predicting the level of TATA element function from the primary sequence.